TIME-SCALES OF HYBRIDISATION OF MAGMATIC ENCLAVES IN REGULAR AND CHAOTIC FLOW FIELDS: PETROLOGIC AND VOLCANOLOGIC IMPLICATIONS - Petrelli M.; Perugini D.; Poli G. (My University, 2006)
This paper describes numerical models of advection/diffusion between enclaves and host magmas, applied with the aim of estimating time-scales during which enclaves can be homogenised. In particular, advection was simulated using a numerical system consisting of regular and chaotic regions. Results indicate that the homogenisation time of enclaves in chaotic regions is several orders of magnitude faster than in regular regions. For instance, an enclave with a diameter of 100 cm may be homogenised in the chaotic region in ~ 380 years, assuming an advection velocity of 10 cm/year, whereas in the regular region it would require 6.5×105 years for complete homogenisation. This implies that, in the same magmatic system, large differences in the degree of homogenisation may co-exist, generating magmatic masses with large spatial and temporal inhomogeneities. The results of this study may have significant petrological and volcanological implications. From a petrological point of view, mafic enclaves dispersed in felsic host rocks are regarded as portions of mafic magma which, trapped inside regular regions, survived the hybridisation process. Instead, host rocks are regarded as regions where efficient mixing dynamics generated hybrid magmas. The fact that a single magmatic mass may display large compositional differences at the same time undermines the assumption of most geochemical models, which assume the temporal and spatial homogeneity of the magma body. From the volcanological perspective, the presence of magmatic enclaves in volcanic rocks allows us to estimate the mixing times of magmas by analysing chemical diffusion patterns between host rocks and enclaves.
Keywords: MAGMATIC ENCLAVES; MAGMA MIXING; CHAOTIC DYNAMICS; DIFFUSION; NUMERICAL SIMULATION; TIMESCALES